Digital Leadership in the Era of Industrial Revolution 4.0: Challenges and Opportunities in Indonesia - Bekti, Herijanto; Pancasilawan, Ramadhan; Komara , Syifa Rachmania (Journal of Ecohumanism, 2024)
Industrial Revolution 4.0 has brought significant changes in various sectors, including in the field of leadership. This research aims to explore the challenges and opportunities faced by leaders in Indonesia in implementing digital leadership. The research results show that the main challenges faced by leaders are a lack of technological infrastructure, resistance to change, and a lack of digital skills among the workforce. However, the research also identified a number of opportunities, including increased operational efficiency, the ability to make data-based decisions, and opportunities for innovation and service. This research provides strategic recommendations for leaders in Indonesia to overcome these challenges and take advantage of existing opportunities, so as to increase company competitiveness in the digital era.